STATES OF THE SPIN SWITCHES ON THE BASE OF SUPERCONDUCTOR/FERROMAGNET MULTILAYERED STRUCTURES - V. N. Kushnir (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The critical temperatures and wave functions of superconducting critical states in the superconductor/ferromagnet structures have investigated on the base of Usadel equation formalism for full configuration sets of spin quantization axes parallel or opposite to the fixed direction. The overturn effect of quantization axes on the critical state amplitude and phase characteristics has established.